Service Employees’ Expressions of Emotions in Restaurants: A Transcendental Phenomenology Study - ISLAM, Mohammad Shahidul; AZIZZADEH, Fariba; ZUPOK, Sebastian; BABAPOUR, Hassan; SOBOŃ, Janusz; ROGOZIŃSKA-MITRUT, Joanna; HOSSEINIi, Aziz; JONES-ESAN, Lawrence (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
As a topic, nonverbal communication ( e.g., expressions of emotions) remains inadequately focused on tourism and hospitality research. Its qualitative significance in service encounters is also virtually unexplored. Given the importance of employees' display of affective characteristics as vivid outcomes of nonverbal communication, i.e., responsiveness, friendliness, trustworthiness, competence, and compassion toward customers, the current study aims to explore customers' experiences toward nonverbal communication of employees during service encounters. By using transcendental phenomenology as a methodological framework, the study resorted to in-depth interviews with 13 customers, representing different nationalities, with whom the study found nonverbal communication as expressions of "body signal, mood, icon, marketing aids, mind changer and anything unspoken" that are conceived quickly and make customers feel welcome and comfortable. The study also found realistic experiences that customers could take their meals at home; they visited the restaurant for having different experiences: refreshment and relaxation while dining. In that emotional situation, they expected favourable nonverbal behaviour instead of a worried face, ignorance, mouse on the floor. The discussion of results is carried out concerning the characteristics of nonverbal communication and the theory of emotional contagion.